The main foreign policy factors of Kazakhstan’s country image formation - Babazhanova Д.М.; Takhan С.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article looks into the significance of key events that have contributed to Kazakhstan’s positive image in the international arena over the last three decades. Important international events such as the Nevada-Semey movement, Nur-Sultan processes, and the Zhusan operation are evaluated in greater detail. Based on the analysis of the course and outcome of these international actions by Kazakhstan, conclusions are drawn on the international recognition of the vectors chosen by our country as positive in terms of harmonizing relations with the world community. The article emphasizes the importance of Kazakhstan’s well-navigated multilateral course of diplomacy based on contractual frameworks. Significant attention is paid to the analysis of the statements by authoritative world figures about Kazakhstan’s image-building foreign policy initiatives and successful strategies that created its favorable image for cooperation.